Design and Synthesis of New Non-Steroidal Anti-inflammatory Agents with Expected Selectivity toward Cyclooxygenase-2 Inhibition - A. Abdul Razzak, Nadeem; F.Hussan, Samera; J. Qaseer, Ahlam (Iraqi Journal of Pharmaceutical Sciences, 2017)
This study includes design and synthesis of new non-steroidal anti-inflammatory agents (NSAIDs) with expected cyclooxygenase-2 (COX-2) selective inhibition to achieve better activity and low gastric side effects. Two series of compounds have been designed and synthesized as potential NSAIDs,these are: Salicylamide derivatives (compounds 3,4,5 ) and Diflunisal derivatives (compounds 10&11). In vivo acute anti-inflammatory effect of one of the synthesized agents (compound 3) was evaluated in the rat using egg-white induced paw edema model of inflammation. Preliminary pharmacological study revealed that compound 3 exhibited less anti-inflammatory effect compared to that of aspirin after 120 and 210 minutes, which encourage the continuation of the search to demonstrate or identify the preliminary pharmacological activity for the synthesized compounds and to identify their selectivity toward COX-2 isoenzymes. Keywords:nonsteriodal anti-inflammatory drugs(NSAID),aspirin derivatives ,diflunisal, Cyclooxygenase -1(cox-1),cyclooxygenase-2(cox-2)